Pengaruh Gaya Belajar Terhadap Prestasi Belajar Siswa Di SMP Negeri 4 Banda Aceh - Cut Ayis Anggina; Yenni Agustina; Geta Ambartiasari (CV. Rumoh Aceh Publishing, 2025)
This research aims to determine the influence of learning style on student on student learning achievement at SMP Neegri 4 Banda Aceh.This research uses descriptive quantitative research.The population in this study consisted of 162 seventh-grada students from 5 classes in the academic year 2023-2024.Using the sloving formula calcaulation, a sample of 30 students was randomly selected.Data collection techniques includd Observation,research results show that the validity and reliability teste of the instrument tems were declared valid because they had a high correlation with the total score and were statistically significant.The reliability test using Cronbach`s Alpha formula yielded 0.873 > 0.70, which also indicates that the instrument used has a very good (reliable) level of reliability. In the classical normality test assumption,Asymp. Sig= 0.436 > 0.05. This proves that the learning style data is normally distributed and has met the requirements for simple linear regression analysis. Based on the results of the simple linear regression test using IBM SPSS Statistiv version 18.0, the tcount-test yielded a value of t= 0.731 < ttable and sig= 0.4871 > 0.05 thus, the influence og learning style on learning achievement does not have a statistically significant effect. This means, formality, that learning style does not contribute strongly enough to explain the variation in student learning achievement in general, so it can be concluded that student learning style does not influence student learning achievement at SMP Negeri 4 Banda Aceh